The growth, determinants, and profitability of nontraditional activities of Chinese commercial banks. Issue 4 (2nd May 2016) - Firth, Michael; Li, Wei; Shuye Wang, Steven
Abstract : Using a panel data set for China's commercial banks between 1998 and 2007, we investigate the relation between a bank's nontraditional income ratio and its operational and financial characteristics after controlling for ownership type, government policy changes, and cross-regional institutional environment differences. We find that banks with narrow net interest margins have stronger incentives to develop nontraditional activities. Moreover, banks located in regions with less local government intervention have fewer nontraditional banking activities. We find evidence that the ownership type of the bank has some influence on the pursuit of nontraditional activities. Nontraditional income has not led to improved bank profitability and we present some conjectures on why this is so. In contrast to the results reported in prior research, we find that the financial performance of the big-four state-owned banks is not inferior to the performance of other banks.